2016
DOI: 10.31018/jans.v8i1.746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicate solubilizing bacteria and fly ash on silicon uptake and yield of rice under lowland ecosystem

Abstract: A field experiment was conducted in sandy loam soils of eastern farm, Agricultural Engineering College and Research Institute, Kumulur, Tamil Nadu, India to study the effect of silicon on yield and uptake of rice (var. BPT 5204) during Kharif season of 2010-11 by taking the treatment combinations based on graded levels of Fly Ash (FA), Silicate Solubilizing Bacteria (SSB) and Farm Yard Manure (FYM) at fixed fertilizer schedule. The experimental soil (0-15 cm) had pH 7.22; organic C 1.4 %; available Si 66.0 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
2
4
0
1
Order By: Relevance
“…The growth of rice plants measured in terms of root-shoot length and dry weight clearly showed the remarkable effect of NBRISN13 and feldspar amendment by increasing the shoot length, number of spikes, and dry weight in all the treatments as compared to control and RS treated plants (Figure 8). The plant growth promoting ability of NBRISN13 was further intensified on feldspar amendment as reported earlier by Peera et al (2016), where, they showed the growth and yield improvement with Si source and silicate solubilizing bacteria. Feldspar treatment has been reported to confer pathogen resistance by providing physical barrier to pathogen infection or the induction of defense (Shen et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…The growth of rice plants measured in terms of root-shoot length and dry weight clearly showed the remarkable effect of NBRISN13 and feldspar amendment by increasing the shoot length, number of spikes, and dry weight in all the treatments as compared to control and RS treated plants (Figure 8). The plant growth promoting ability of NBRISN13 was further intensified on feldspar amendment as reported earlier by Peera et al (2016), where, they showed the growth and yield improvement with Si source and silicate solubilizing bacteria. Feldspar treatment has been reported to confer pathogen resistance by providing physical barrier to pathogen infection or the induction of defense (Shen et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…Whereas, the mean leaf yield was 5.08 g plant -1 only without microbial inoculants. The results obtained by Peera et al, [23] was in corroboration with the current findings. The control without silicon sources and without bacterial showed a minimum leaf yield.…”
Section: Coriander Leaf Yieldsupporting
confidence: 93%
“…The results are in accordance with [22] who suggested the improvements of Si content in rice seedlings through the application of rice husk ash (RHA) and other soil organic matters. Peera et al, [23] found that the application of SSB with FYM significantly increased the silicon content in rice.…”
Section: Coriander Leaf Simentioning
confidence: 99%
See 1 more Smart Citation
“…In soil, the element Si is primarily present as SiO2, about 50-70% of the mass of the soil, and in various forms of aluminosilicate (Sommer et al, 2006). Although si is abundant in the soil, most of these elements are not available to plants due to the low solubility of the si compounds in the soil (Peera et al, 2016).…”
Section: Silica and Plant Metabolismmentioning
confidence: 99%